Lathrolestes pleuralis Thomson 1883 - Reshchikov, Alexey (Zenodo, 2015)
Lathrolestes pleuralis (Thomson, 1883) Figs. 104–105. Lathrolestus pleuralis Thomson, 1883: 916 –917. Lectotype ♀, MZLU [examined]. Type locality: Sweden (Norrland). Material. 1♀ 1♂, DENMARK, ZMUC; 1♀, NORWAY, Akershus, Ullensaker, Sessvollmoen, Aurtjernet W, 26.VI–25.VIII.2007, leg. L. O. Hansen, ZMUN; 1♀, SWEDEN, Gästrikland, NHRS; 4♀, SWEDEN, Lappland, Sorsele kommun, Ammarnäs, Vindelfjällens naturreservat, Tjulträsklaspen, Alpine birch wood. N65°58.007, E16°03.630 (=TrapID 46) 26.vii–15.viii.2004 (=coll. event ID 1201), leg. SMTP, NHRS; 2♀, SWEDEN, Uppland, Älvkarleby kommun, Båtfors. Pine forest w. blueberry. N60°27.639´E17°19.069´(=Trap ID 7), 17.vi–03.vii.2003 (=coll. event ID 378), leg. SMTP, NHRS; 1♀, SWITZERLAND, NHRS-HEVA000002033, NHRS. Diagnosis . This species differs from other species of the genus by the following character states: 1) clypeus projecting distinctly anteriorly, but not strongly, and not incurved, 2) head narrowed behind eyes, 3) occipital carina incomplete dorsally, 4) areolet petiolate, 5) tarsal claws pectinate, teeth shorter than apical tooth, 6) hind femur yellowish, 7) carinae of propodeum absent, 8) parameres elongate and wider apically. Distribution . Denmark *, Finland, Germany, Latvia, Norway, Russia (Chita Oblast, Kamchatka, Khabarovsky Kray, Primorsky Kray, Sakha Yakutia), Sweden, UK. Published as part of Reshchikov, Alexey, 2015, Review of North European species of the genus Lathrolestes (Hymenoptera, Ichneumonidae) with description of one new species from Öland (Sweden), pp. 1-47 in Zootaxa 4033 (1) on page 36, DOI:10.11646/zootaxa.4033.1.1, http://zenodo.org/record/289776